A study to explore the motives of investors to invest in derivative markets: A PLS-SEM approach - Manisha Sanghvi; Pankaj Sharma; Arti Chandani (Financial Internet Quarterly, 2024)
The objective of the study is to explore the motives of investors to invest in derivative markets. It is a quantitative study where a survey method was used to collect data from the investors using a probability sampling method. The data was analyzed using PLS-SEM to test the conceptual model. The results of the study show that speculation, hedging, and financial literacy are strong predictors of investorsḿotives to invest in the derivatives market. The R2 was 0.447 implying speculation, hedging, and financial literacy explain 44.7% of the variance of the dependent variable, that is, the motives of investors to invest in equity derivatives, and the adjusted R-square is 0.432 (43.2%) which validates the model. Few studies explore the reasons to invest in derivatives using secondary data. However, to the best of the authorś knowledge studies exploring the motives of investors are rare, and there have been none using primary data from an Indian perspective. The study provides empirical evidence that could be useful to companies, investors, brokers, and policymakers to understand the motives of investors to invest in derivatives.
Keywords: 330; Speculation; Hedging; Financial Literacy; Motives to Invest; Derivatives; PLS-SEM